Development of an ultra-fast switching charge pumping measurement method - Tan, Edwin Pei Ming. (2009)
Advances in microelectronics has been reflected in the aggressive scaling of MOSFETS and the increased density of transistors in a given wafer area. Device miniaturization results in reduced unit cost per circuit function. As device dimensions decreases, the intrinsic switching time also decreases. Hence, increased device speed is obtained. In addition, energy dissipation per device also reduces. However, this does not mean that there are no limitations. In fact, with increased scaling of the device dimensions, reliability issues tend to surface. Reliability issues like NBTI has been known since the 1960s and the problem is more critical in PMOS than in NMOS. NBTI has recently been a problem because of the widespread usage of CMOS (Complementary MOS : Consisting of PMOS and NMOS ). NBTI causes degradation of PMOS device which leads to shifts in absolute threshold voltage caused by interface trap density and oxide traps. Thus, it is crucial to be able to understand the degradation problems inherent in MOSFETs, especially NBTI in PMOS devices. Conventional characterization methods have been used to determine the interface trap density caused by NBTI in PMOS. But NBTI suffers from recovery when negative stress voltage is relaxed at the gate and conventional characterization techniques introduce a significant time delay between stress and measurement. Conventional characterization methods like Charge Pumping, though is a sensitive, powerful and simple technique to study interface trap density of sub-micron MOSFETs, is unable to avoid the pitfall of introducing a time delay between NBTI stress at elevated temperature and measurement. Therefore, the purpose of this FYP is to develop an Ultra – Fast – Switching Charge Pumping technique to measure the interface trap density at the Si-channel /SiO2 –gate oxide with increased accuracy due to the keeping of the time delay to an extremely minimum. With such an accurate characterization method being developed, studies of sub-micron MOSFETs will be more meaningful and information that is missed in the past due to inaccurate techniques may be captured by this Ultra-Fast-Switching Charge Pumping method.